2014
DOI: 10.1038/cddis.2014.474
|View full text |Cite
|
Sign up to set email alerts
|

CBAP promotes thymocyte negative selection by facilitating T-cell receptor proximal signaling

Abstract: T-cell receptor (TCR)-transduced signaling is critical to thymocyte development at the CD4/CD8 double-positive stage, but the molecules involved in this process are not yet fully characterized. We previously demonstrated that GM-CSF/IL-3/IL-5 receptor common β-chain-associated protein (CBAP) modulates ZAP70-mediated T-cell migration and adhesion. On the basis of the high expression of CBAP during thymocyte development, we investigated the function of CBAP in thymocyte development using a CBAP knockout mouse. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 54 publications
0
5
1
Order By: Relevance
“…Our previous studies have reported the pro-apoptotic functions of CBAP in cytokine-dependent cell lines [22] or in primary hematopoietic cells [24, 25]. However, in the current study, we have discovered an important oncogenic and pro-proliferative role of CBAP in malignant hematological cells, such as T-ALL cells.…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations
“…Our previous studies have reported the pro-apoptotic functions of CBAP in cytokine-dependent cell lines [22] or in primary hematopoietic cells [24, 25]. However, in the current study, we have discovered an important oncogenic and pro-proliferative role of CBAP in malignant hematological cells, such as T-ALL cells.…”
Section: Discussioncontrasting
confidence: 52%
“…Previous studies have shown that CBAP is involved in ZAP70-dependent Vav1 phosphorylation and β1 integrin signalosome activation in chemokine-induced inside-out signaling [24]. It is also involved in LAT-PLCγ2-ZAP70 signalosome formation during TCR engagement [25]. We have previously mapped two discrete binding sites for Vav1 and Zap70 in the N-terminus of CBAP, as well as a β1 integrin binding site in the C-terminal half of the CBAP protein [24], but their functions remain unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The candidate genes for further survey included glypican-1 (GPC1) [ 14 ], cyclophilin B (CYPB) [ 15 ]. Mesothelin (MSLN) [ 16 ], LIM domain kinase 2 (LIMK2) [ 17 ], dedicator of cytokinesis 4 (DOCK4) [ 18 ], serine/threonine kinase 31 (STK31) [ 19 ], insulin-like growth factor-1 (IGF1) [ 20 ], chitinase 3-like 1 (CHI3L1) [ 21 ], survivin [ 22 23 24 25 ], and transmembrane protein 102 (TMEM102) of common beta-chain-associated protein (CBAP) [ 26 ].…”
Section: Methodsmentioning
confidence: 99%